2015
DOI: 10.1007/s00441-015-2203-y
|View full text |Cite
|
Sign up to set email alerts
|

Lack of galectin-3 up-regulates IgA expression by peritoneal B1 lymphocytes during B cell differentiation

Abstract: Galectin-3 is a β-galactoside-binding protein with an inhibitory role in B cell differentiation into plasma cells in distinct lymphoid tissues. We use a model of chronic schistosomiasis, a well-characterized experimental disease hallmarked by polyclonal B cell activation, in order to investigate the role of galectin-3 in controlling IgA production through peritoneal B1 cells. Chronically infected, galectin-3-deficient mice (Lgals3 −/− ) display peritoneal fluid hypercellularity, increased numbers of atypical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…Gal-3 has been described as significant regulator of B cell differentiation 3 , 4 , 7 , 8 . However, the molecular and cellular mechanisms involved are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gal-3 has been described as significant regulator of B cell differentiation 3 , 4 , 7 , 8 . However, the molecular and cellular mechanisms involved are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…In non-conventional peritoneal B1 lymphocytes biology, gal-3 also plays regulatory roles in the differentiation of both B1a and B1b cells into plasma cells by IL-5 and Blimp-1 signaling-dependent manner 5 . Clearly, gal-3 interferes with B cell compartments in distinct lymphoid organs 4 8 . However, the mechanisms that correlate gal-3 with molecular pathways during bone marrow B lymphopoiesis, peripheral mobilization and settlement mainly in the spleen, are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…An inhibitory role of galectin-3 was demonstrated in a model of galectin-3 knockout mouse, where B lymphocytes of the peritoneal cavity favored differentiating into plasma cells [ 153 ]. More specifically, a significant increase of IgA-producing cells in the peritoneal cavity was observed in comparison to galectin-3-expressing mice during chronic schistosomiasis as well as in response to interleukin-5 and transforming growth factor-β [ 154 ]. Although the mechanisms of galectin-3-dependent inhibition of B cell differentiation are obscure, a recent study revealed that Notch signaling pathways might play an important regulatory role [ 155 ].…”
Section: Galectin-3mentioning
confidence: 99%
“…In accordance, B1 cells may modulate their adhesion molecules and differentiate into plasma cells still in the peritoneal cavity. On the other hand, these cells can adhere to mesenteric membranes or omentum, as described in the literature, if previously activated by the absence of galectin-3 [26].…”
Section: B1 Cellmentioning
confidence: 91%
“…In addition to the constitutive expression of STAT3 by B1 cells, and in contrast to B2 cells, these cells also express the interleukin-5 receptor alpha (IL-R5α) chain, which renders to this subset the ability to specifically respond to interleukin 5 (IL-5), GM-CSF, and IL-3 [29]. In this way, B1 lymphocytes can be maintained in vitro if properly stimulated by IL-5 allowing the analysis of their behavior such as the proliferation rate, survival, and/or differentiation into Ig-producing cells and IgA switch under experimental conditions [26,30,31].…”
Section: B1 Cellmentioning
confidence: 99%